Analisa Bentuk Bahasa Pada Penderita Afasia Broca - Agustina Agustina; Nining Lestari (Jurnal Terapi Wicara, 2023)
Aphasia is an acquired language disorder resulting from a lesion in the part of the brain that regulates language. Broca's aphasia as one of the aphasia syndromes is a type of aphasia that often appears. Broca's aphasia is non-fluent aphasia, there are problems in communicating due to deficits in language forms, in the form of problems with phonology, morphology and syntax. Output verbally disturbed mild to severe. The aim of this research is to know the form of language phonologically, morphologically and syntactically in patients with Broca's aphasia. This study used a qualitative case study type method, in which the researcher conducted an in- depth exploration of 10 language samples with Broca's aphasia. The study used the Aphasia Test instrument for Diagnostic Information and Rehabilitation (TADIR). Broca's aphasia sufferers show a significant reduction in the form of their language, in the form of disturbances in phonology (phonemic), morphology, and syntax